The Effect of E-Modules with Scaffolding on Students' Problem Solving Ability in Static Fluid Material: Pengaruh E-Modul dengan Scaffolding terhadap Kemampuan Pemecahan Masalah Peserta Didik pada Materi Fluida Statis - Rizkyanti, Elta; Supriana, Edy; Latifah, Eny (SEJ (Science Education Journal), 2024)
This research aims to determine the effect of e-modules with scaffolding on students' problem solving abilities in static fluid material. The method used is quasi-experimental with a one group pretest-posttest approach. Research was carried out at a high school in Surabaya in class XI MIPA in the 2023/2024 academic year by providing 10 essay questions. Based on the research that has been carried out, the results obtained are that after using the e-module with Scaffolding, students experienced an increase in problem solving abilities on the Useful Description (UD) indicator and the hydrostatic pressure sub-material. In the UD indicator, the N-Gain was obtained at 0.822 in the high category and in the hydrostatic pressure sub-material, the N-Gain was obtained at 0.693 in the high category. Improvements also occurred in four other indicators in the middle and low categories, these indicators are Physics Approach (PA), Specific Application of Physics (SAP), Mathematical Procedure (MP), and Logical Progression (LP) in each material. To dig deeper into unknown aspects, further research can explore the factors that influence high or low indicator changes in each static fluid sub-material and add qualitative data to strengthen the research results.